A PSICOMOTRICIDADE COMO ALICERCE NO DESENVOLVIMENTO DA LEITURA E DA ESCRITA - Aparecida Rodrigues Freire, Maria; Soares Freire Germano, Marlene (LINKSCIENCEPLACE, 2026)
The present article aims to highlight the need for the child’s psychomotor development to promote reading and writing learning. The qualitative study sought to base the bibliographical research through analysis and dialogues between the various literatures that approach the theme. Psychomotricity is one of the essential and indispensable pillars for an overall and uniform development of the child, playing a very important role in the learning process, since that while exploring the environment in which the it lives, the child makes use of senso-perceptive-motor skills,central elements to the psychomotor approach to the construction of their interaction, learning and personality, highly determinant factors in the structuring of the being and its psychosocial relationships. The process of learning takes place in a specific and different way, since each one elaborates their perceptions according to their existential universe, but the child, during reading and writing learning process, needs a stimulating environment that supports its development once its body is already structured and well developed. Psychomotricity, therefore, allows children to situate themselves in space and time in a playful way as it develops certain skills, becoming essential in their process of cognitive development.